Diseminasi Teknologi Pemanfaatan Asap Cair dalam Produksi Pertanian dan Pangan Lokal Secara Berkelanjutan - Adhiguna, Rizky Tirta; Robbani, Syifa’; Aulia, Nurul Izzah; Haryani, Fatria Resti; Setyaaji, Primayoga Harsana; Puspitahati, Puspitahati; Rejo, Amin; Kuncoro, Endo Argo (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Lack of understanding of using liquid smoke in preserving chicken fillet food and rubber agricultural products for durability among farmers in Payakabung Village, North Indralaya District, Ogan Ilir Regency is the main factor in carrying out Community Service (PkM). The purpose of this PkM is to educate and improve the knowledge and skills of the Payakabung Village community regarding the benefits and techniques of using liquid smoke on chicken fish meat as a food preservative and agricultural products for the durability of rubber latex products. Implementing community service for farmers is done directly in the field through pedagogical and participatory learning. The activity is counselling and socialization through lecture methods, discussions, and questions and answers, where the community service team delivers the material. Community Service related to the dissemination of liquid smoke technology in Payakabung Village has effectively empowered the local community, especially farmers. Through this program, farmers have succeeded in developing skills in utilizing liquid smoke on chicken fillets and rubber agricultural products for the durability of latex, which has high economic value. The program's success is reflected in farmers' ability to use liquid smoke independently to preserve and improve the quality of products such as chicken fillets and rubber, ultimately opening up new business opportunities and increasing their income.